The potential benefits of using videos in higher education - Vieira, Isabel (2014)
The developments of digital technology have opened new outlooks for online education which offer students the flexibility to learn at any time and any place. With all this instructional changes instructors, in all levels of the educational chain have been compelled to adapt quickly to this reality. They have a wide diversity of tools available to grab student’s attention and motivate them to embrace the knowledge in their own learning process. One of these resources is the use of videos. Through them lecturers can deliver complex information and contents to students and, if used creatively, videos can become a powerful technological tool in education. In this article we will explore some of the potential benefits and challenges associated with the use of videos in the teaching and learning process at higher education levels. We will also discuss some thoughts and examples for the use of teaching materials to enhance student’s learning and try to change ideas about the potentialities and future of video’s annotation new software resources, as incoming open tools for group work involvement.